2000
DOI: 10.1161/01.atv.20.3.624
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Osteopontin in Human Diabetic Artery and Analysis of Its Functional Role in Accelerated Atherogenesis

Abstract: Abstract-We have previously reported that high glucose stimulates osteopontin (OPN) expression through protein kinase C-dependent pathways as well as hexosamine pathways in cultured rat aortic smooth muscle cells. The finding prompted us to study in vivo expression of OPN in diabetes mellitus. In the present study, we found by immunohistochemistry that medial layers of the carotid arteries of streptozotocin-induced diabetic rats and the forearm arteries of diabetic patients stained positively for OPN antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 38 publications
8
78
1
4
Order By: Relevance
“…This accumulation is seen in the tunica media from areas of the tissue with and without atherosclerotic plaques. The accumulation of osteoprotegerin throughout the deeper layers of the vessel wall may reflect generalised changes in the arterial system in diabetes, as part of diffuse arterial changes such as alterations in glycoproteins [31], collagens [32] and glycosaminoglycans [33]. In addition, osteoprotegerin may be related to the development of medial calcification, which is frequently present in patients with diabetes [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation is seen in the tunica media from areas of the tissue with and without atherosclerotic plaques. The accumulation of osteoprotegerin throughout the deeper layers of the vessel wall may reflect generalised changes in the arterial system in diabetes, as part of diffuse arterial changes such as alterations in glycoproteins [31], collagens [32] and glycosaminoglycans [33]. In addition, osteoprotegerin may be related to the development of medial calcification, which is frequently present in patients with diabetes [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, hypertension and DM could synergistically deteriorate diastolic function in human. Kawamura et al 13 previously reported that OPN expression is upregulated in diabetic human and rat vascular walls. In addition, OPN deletion attenuated diastolic dysfunction in heart of streptozotocin-induced diabetic mouse model.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 97%
“…11,12 More recently, OPN has emerged as an important protein involved in cardiovascular diseases, including post-myocardial infarction (MI) remodeling and atherosclerosis. 13,14 OPN is expressed at low level under physiological condition in heart; however, its expression is markedly increased after MI and cardiac hypertrophy. 14,15 Overexpression of OPN in mouse cardiomyocyte induces cardiac dysfunction, dilation and fibrosis in heart, 16 suggesting its expression is closely related to myocardial function and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…1A), although nondiabetic animals exhibit a robust skeletal Msx2 induction (in preparation). High fat diets up-regulate aortic expression of osteogenic gene programs, reflected in the levels of OPN and Msx2 expression (15,16,32); however, PTH(1-34) suppressed aortic expression of OPN and Msx2 by ϳ50% (Fig. 1B).…”
Section: Pth(1-34) Up-regulates Skeletal Osteopontin Gene Expression mentioning
confidence: 97%